Effects of ambient methanol on pollutants formation in dual-fuel spray combustion at varying ambient temperatures: A large-eddy simulation. (1st December 2020) - Xu, Shijie; Zhong, Shenghui; Pang, Kar Mun; Yu, Senbin; Jangi, Mehdi; Bai, Xue-song
Abstract: Large-eddy simulation with a finite-rate chemistry model is carried out to investigate the formation of soot and nitrogen oxides (NOx) in the dual-fuel spray combustion. Liquid n-heptane is injected into a constant volume chamber, filled with a premixed methanol–air mixture with an equivalence ratio ( ϕ m ) of 0.3. Three dual-fuel cases are simulated under initial temperatures of 900, 950 and 1000 K. Three single-fuel cases, with the same configurations, but with pure air being used as ambient gas composition are also simulated and used as baselines for comparison purposes. The paper aims to identify the main mechanisms of soot and NOx reduction in dual-fuel spray combustion under conditions relevant to internal combustion engines. The numerical model is validated using the Engine Combustion Network n-heptane fuel experimental data. It is found that soot emission has a strong non-linear dependence on ambient temperature in dual-fuel combustion. At high temperatures, soot emission is enhanced whereas at lower temperatures, it is suppressed. For the presently studied cases, the results show that the enhanced mixing is the primary reason for soot reduction in the 900 and 950 K cases, whereas the onset auto-ignition in ambient methanol/air mixture, which leads to a shortened lift-off length of the n-heptane spray flame and reduced ambient oxygen concentration, is the mechanism behind the enhanced soot emission in the 1000 K case. The methanol dilution effects of oxygen concentration and heat capacity on ignition delay time and the maximum flame temperature are minor in the current dual-fuel configurations. Regarding NOx emission in dual-fuel combustion, it is found that the effect of methanol on NOx formation also depends on the ambient temperatures. The NOx formation rate in the dual-fuel case is lower than that of the single-fuel case at 900 K. However, an opposite trend of NOx formation rate is observed in the 1000 K cases. The main reason for the increased NOx emission is the larger high temperature region resulted from the interaction of the spray flame and the ambient mixture ignition. Highlights: Modes of n-heptane/methanol dual-fuel combustion are analyzed using LES. A suppression effect of methanol on n-heptane ignition is observed and explained. A non-monotonic dependence of soot and NOx emission on T amb is identified. Mechanisms of NOx and soot emissions in dual-fuel combustion are analyzed.